Missouri - Lago, Mary Ellen; Baker, Vicky; Matusevich, Melissa N (New York Children's Press, 2003)
Takes the reader on a tour of the state once called the "Gateway to the West," emphasizing its geography, history, government, and culture
Introducing Missouri -- The land of Missouri -- Missouri through history -- Governing Missouri -- The people and places of Missouri
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: Missouri -- Juvenile literature; Missouri